2015
DOI: 10.1016/j.bmcl.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of oligodeoxyribonucleotides modified with 2′-thio-2′-deoxy-2′-S-(pyren-1-yl)methyluridine

Abstract: Pyrene-functionalized oligonucleotides are intensively explored for applications in materials science and diagnostics. Here, we describe a short synthetic route to 2′-S-(pyren-1-yl)methyl-2′-thiouridine monomer S, its incorporation into oligodeoxyribonucleotides (ONs), and biophysical characterization thereof. Pseudorotational analysis reveals that the furanose ring of this monomer has a slight preference for South-type conformations. ONs modified with monomer S display high cDNA affinity but decreased binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…20 In fact, we have shown that Invader probes based on the 2′- O -(pyren-1-yl)methyl-RNA chemistry can be used for recognition of mixed-sequence chromosomal DNA targets at non-denaturing conditions. 26 Recently, we have carried out a series of systematic structure-property studies aiming at improving the dsDNA-recognition efficiency of Invader probes and have thus examined the impact of different nucleobases, 27 relative intercalator orientations, 28 intercalator-sugar linkers, 20 sugar skeletons, 20,29 backbones and probe architectures. 26,3032 …”
Section: Introductionmentioning
confidence: 99%
“…20 In fact, we have shown that Invader probes based on the 2′- O -(pyren-1-yl)methyl-RNA chemistry can be used for recognition of mixed-sequence chromosomal DNA targets at non-denaturing conditions. 26 Recently, we have carried out a series of systematic structure-property studies aiming at improving the dsDNA-recognition efficiency of Invader probes and have thus examined the impact of different nucleobases, 27 relative intercalator orientations, 28 intercalator-sugar linkers, 20 sugar skeletons, 20,29 backbones and probe architectures. 26,3032 …”
Section: Introductionmentioning
confidence: 99%
“…Owing to these unique predictable properties, the 2′- O -(pyrene-1-yl)methyl-modified nucleotide monomers have been used as components of highly sensitive probes in a number of fluorescent approaches to RNA detection [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 ], as SNP-discriminating RNA-specific fluorescent probes [ 48 , 49 ], as key components in highly-fluorescent pyrene π-stack arrays on RNA ( Figure 2 b) ( Section 2.3.6 ) [ 46 , 50 , 51 , 52 , 53 , 54 , 55 ], and also as intercalating units efficiently stabilizing DNA:DNA duplexes ( Section 3.2 ) [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. The properties and applications of the oligonucleotides comprising 2′- O -(pyren-1-yl)methylribonucleotides monomers have been discussed in detail in the just published review [ 64 ].…”
Section: Fluorescent Biosensorsmentioning
confidence: 99%
“…Hrdlicka and coworkers have introduced so-called Invader probes, i.e., short dsDNA probes that are energetically activated through modification with one or more +1 interstrand zipper arrangements of pyrene-modified nucleotides ( Figure 36 ) [ 17 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 237 , 238 , 239 , 240 ].…”
Section: Agents For Targeting Of Dsdnasmentioning
confidence: 99%
See 2 more Smart Citations